2018
DOI: 10.1097/acm.0000000000002081
|View full text |Cite
|
Sign up to set email alerts
|

Managing Multiplicity: Conceptualizing Physician Cognition in Multipatient Environments

Abstract: The authors propose a conceptual framework for how EPs prioritize care for multiple patients in complex environments. This study may be useful to teachers who train physicians to function more efficiently in busy clinical environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Our data also show similar results: as skill level increased, the number of patients discharged increased, representing a clear correlation of experience level and multi-patient care. This difference was less apparent among residents and attending physicians who likely demonstrate very similar approaches to multiple patients (Chan et al, 2018). It should be pointed out that multi-tasking -even when manifested in this serious game simulation -is actually task-switching (Skaugset et al, 2016); VitalSigns had a finite screen space and the game mechanic of only being able to view one patient at a time.…”
Section: Critical Thinking / Multi-tasking Measuresmentioning
confidence: 86%
See 2 more Smart Citations
“…Our data also show similar results: as skill level increased, the number of patients discharged increased, representing a clear correlation of experience level and multi-patient care. This difference was less apparent among residents and attending physicians who likely demonstrate very similar approaches to multiple patients (Chan et al, 2018). It should be pointed out that multi-tasking -even when manifested in this serious game simulation -is actually task-switching (Skaugset et al, 2016); VitalSigns had a finite screen space and the game mechanic of only being able to view one patient at a time.…”
Section: Critical Thinking / Multi-tasking Measuresmentioning
confidence: 86%
“…Furthermore, the game employed a multiple choice option for diagnoses, instead of writing a diagnosis de novo, which may lead to a higher correct diagnosis rate (Chang et al, 2017). In addition, the literature on multi-patient environments by Chan et al have shown a similarity in patient approach among residents and experts, which consist of strategies that are quite alike in overall vision, individual patient review, and prioritization at the patient level (Chan et al, 2018). Given the similarity in strategy, it is likely that multi-patient approaches among the residents and attendings worked similarly with the patient portfolio developed to match a typical PED.…”
Section: Accuracy Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our secondary analyses, efficiency and accuracy within a simulated clinical setting appear to be intertwined. Chan et al notes that “multipatient management” is not simply multitasking, and that strategies to manage multiple patients in a game setting requires different skill domains (Chan et al, 2018, 2019). Our secondary analyses provide evidence for this assertion, as the efficiency metrics are quite related to the metrics requiring clinical knowledge and application.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al proposes that trainees require not just “managerial skills” but also the grasp on medical decision-making and case complexity . (Chan et al, 2017, 2018, 2019). Ledrick et al also note that raw multitasking plays a lesser factor than clinical experience among EM resident efficiency in an ED (2009).…”
Section: Discussionmentioning
confidence: 99%